Arduous admissions and a precarious profession: student teachers' pre-admission demotives. Issue 3 (27th May 2022) - Mankki, Ville; Kyrö-Ämmälä, Outi
ABSTRACT: Sustaining the attractiveness of the teaching profession to recruit committed students to teacher education is a global policy issue. However, in many parts of the world, the teaching profession has become less attractive. Also in Finland, where teacher education has traditionally been highly attractive, several programmes have recently suffered from a substantial decrease in the number of applicants. The current paper addresses the phenomenon by investigating student teachers' pre-admission demotives. A total of 146 freshly admitted student teachers in primary teacher education in two universities wrote texts concerning the reasons for turning down primary teacher education and the profession during the application period. Thematic qualitative analysis revealed that demotives were connected to 1) arduous admissions, 2) deterministic training and 3) a precarious profession. The majority (54%) of participants expressed demotives connected to the above themes: concerns about the profession were the most frequent followed by doubts concerning admissions. By focusing on demotives the study fills the current gap in existing literature. The results can be implemented when outlining the measures to increase the attractiveness of the teaching profession, developing recruitment strategies and admission procedures, and designing more effective and meaningful teaching and learning in teacher education.